1989
DOI: 10.1161/01.hyp.13.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Mixture analysis of erythrocyte lithium-sodium countertransport and blood pressure.

Abstract: This study employs multivariate normal mixture analysis, a technique for identifying discrete subgroups within populations, to examine the relation of erythrocyte lithium-sodium (RBC Li + -Na + ) countertransport and blood pressure in a group of 474 healthy adults. Received April 11, 1988; accepted September 23, 1988. recently proposed marker for essential hypertension that has been shown to be associated with high blood pressure in many studies 8 -16 and also to be related to organ-scale abnormalities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
(14 reference statements)
1
8
1
Order By: Relevance
“…12 The prevalence of high countertransport is lower (12.9%) in the present population-based sample than in our earlier study (27%), which undoubtedly reflects an overrepresentation of hypertensive subjects in the earlier sample.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…12 The prevalence of high countertransport is lower (12.9%) in the present population-based sample than in our earlier study (27%), which undoubtedly reflects an overrepresentation of hypertensive subjects in the earlier sample.…”
Section: Discussioncontrasting
confidence: 74%
“…As shown in Figure 1, univariate mixture analysis revealed that the distribution of RBC Li + -Na + countertransport is composed of two groups (p<0.00001 versus one or three groups), which is consistent with our earlier findings. 12 The larger subgroup (n=614, 87.1%) has a mean V^ for Li + -Na + countertransport activity ( Table 28 and is referred to below as the "high countertransport" group. Both groups had a similar proportion of males (57.1% versus 54.6%, high versus normal countertransport, p=0.64 by x 2 ), so that no adjustment for gender differences was necessary in the subgroup comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,35 The findings of increased blood pressure and increased indexes of body weight and fat mass as well as an increased waist/hip ratio in subjects with high SLC, are consistent with earlier reports. 4,35 Linkage analysis was performed with SLC used as a quantitative phenotype. The additive heritabilities of SLC-1 and SLC-2 were 0.42 and 0.49, respectively.…”
Section: Weder Et Al Genetic Linkage Of Rbc Sodium-lithium Countertrasupporting
confidence: 91%
“…SLC is continuously distributed with right-skewing in populations, and biometric mixture analysis has suggested that the skewed distribution of SLC is composed of 2 overlapping normally distributed subpopulations. [2][3][4][5] In addition to blood pressure, a number of exogenous factors and traits are associated with variation in SLC activity, including plasma triglyceride 6 and potassium 7 levels, insulin resistance, 8 ethnicity, 9 pregnancy, 10 and nonmodulation of blood pressure in response to changes in dietary sodium. 11 Numerous other potential confounders have been examined, often with inconsistent findings, 12 but it is safe to say that at present, no single trait clearly explains the finding of 2 subpopulations.…”
mentioning
confidence: 99%